Who am I without anorexia? Identity exploration in the treatment of early stage anorexia nervosa during emerging adulthood: a case study. (13th June 2019) - Koskina, A.; Schmidt, U.
Abstract: Emerging adulthood (age 18–25 years) is a distinct developmental phase, characterized by multiple life changes, transitions and uncertainties, associated with significant risk of mental ill health in vulnerable individuals. Identity exploration and development is key during this phase, and the development of an eating disorder during this time can significantly impact on this process. This single-case study details the treatment of an 18-year-old female outpatient with first episode, recent onset anorexia nervosa. Using the Maudsley Model of Anorexia Nervosa Treatment in Adults (MANTRA), focus was placed on identity exploration and development as a tool to reduce the dominance of anorexia nervosa and increase recovery focus. Outcome measures at end of treatment and 6-month follow-up showed significant sustained improvement in BMI and EDE-Q scores. The patient gave detailed positive feedback suggesting that this was a highly acceptable and effective intervention. The case study is discussed with reference to limitations and some reflections on the utility of incorporating identity work in the treatment of anorexia nervosa in emerging adulthood. Key learning aims: (1) This case study is thought to have important clinical implications for tailoring the treatment of early stage AN to the emerging adult population. (2) Identity exploration is a key feature of this developmental stage, and incorporating this work into therapy allows for experimentation and formation of an alternative, healthy set of values, beliefs and behaviours. (3) This case also highlights the value of using role models in the construction of a non-illness driven identity, to support with behavioural change.